1998
DOI: 10.1093/oxfordjournals.deafed.a014354
|View full text |Cite
|
Sign up to set email alerts
|

The Written Language of Deaf Adolescents: Patterns of Performance

Abstract: A study was conducted of the written language skills of a representative sample of 69 adolescents with severe and profound hearing losses, using both a standardized language sample (TOWL-2) and a letter. The overall results confirmed the generally low levels of performance typically found in this population and the existence of a developmental plateau. Nevertheless, performance levels were not uniformly low. The sample scored relatively high on measures of orthographic conventions and on semantics, but conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
1
24
2
Order By: Relevance
“…Orthography for Deaf writers is not an area of challenge and underachievement (Musselman & Szanto, 1998). Hearing bilingual writers frequently make spelling errors because hearing activates phonological processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthography for Deaf writers is not an area of challenge and underachievement (Musselman & Szanto, 1998). Hearing bilingual writers frequently make spelling errors because hearing activates phonological processing.…”
Section: Discussionmentioning
confidence: 99%
“…From the descriptive statistics (Table 10) we can see that there were three times more verb omissions in the translation task than the direct composition. Finally, on the error analysis level, there are interesting findings with respect to orthography, as Deaf school students' orthography has not been noted as an area of major difficulty (Musselman & Szanto, 1998). When orthography was analysed there was a significant task effect on 'misselection' errors.…”
Section: Error Analysis: Types Of Errorsmentioning
confidence: 96%
“…In the study by Musselman and Szanto (1998), hearing-impaired students enrolled in resource room programs and mainstreamed settings scored higher in semantic and convention skills; however, their scores in grammar use were rather low. The results of the study showed that the scores of the students enrolled in the Auditory/Oral (AO) program were higher than those enrolled in the Total Communication (TC) program.…”
Section: Introductionmentioning
confidence: 86%
“…However, the number of studies on hearing-impaired students enrolled in public schools was found to be limited. In the existing studies, evaluations were made of the writing skills of hearing-impaired students that spent a certain amount of time in formal education classes (Antia, Jones, Reed & Kreimeyer, 2009;Antia et al, 2005); the writing tasks of students enrolled in resource room programs and mainstream settings were analyzed (Musselman & Szanto, 1998;Spencer et al, 2003), various inclusion programs were examined (Most et al, 2006), and hearing-impaired students, who attended self-contained classrooms, were discussed in terms of their writing skills (Easterbrooks & Stoner, 2006;Wolbers, 2007). In the study by Antia et al (2005) on 110 hearing-impaired students, who were enrolled in public schools, students were found to perform within the low mean score levels in contextual conversions, contextual language, and story construction sub tests.…”
Section: Introductionmentioning
confidence: 99%
“…But these limitations might not be the only ones that contribute to their literacy impairment. Reading education typically shifts from single word decoding to sentence comprehension at around age 9 (Gaustad & Kelly, 2004), which interestingly coincides with the age that deaf adolescents frequently fail to progress (Allen, 1986;Musselman & Szanto, 1998). Therefore, apart from phonological challenges at the word level, another type of challenge for reading arises at the level of morpho-syntax.…”
mentioning
confidence: 93%